2021
DOI: 10.1038/s41419-021-03803-8
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-secreted exosomal miR-21-5p induces angiogenesis and vascular permeability by targeting KRIT1

Abstract: Cancer-secreted exosomes are critical mediators of cancer-host crosstalk. In the present study, we showed the delivery of miR-21-5p from colorectal cancer (CRC) cells to endothelial cells via exosomes increased the amount of miR-21-5p in recipient cells. MiR-21-5p suppressed Krev interaction trapped protein 1 (KRIT1) in recipient HUVECs and subsequently activated β-catenin signaling pathway and increased their downstream targets VEGFa and Ccnd1, which consequently promoted angiogenesis and vascular permeabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 45 publications
0
54
0
Order By: Relevance
“…Tumor-derived EVs are thought to regulate protumoral functions of endothelial cells in numerous types of cancers including hepatocellular carcinoma (HCC) ( Lin et al, 2018 ), colorectal cancer ( Huang and Feng, 2017 ; Zeng et al, 2018 ; He et al, 2021 ), cervical cancer ( Wu et al, 2019 ), nasopharyngeal carcinoma ( Bao et al, 2018 ; Tian et al, 2021 ; Zhang K. et al, 2021 ), glioma ( Ma et al, 2017 ; Wang Z.-F. et al, 2019 ), and lung cancer ( Hsu et al, 2017 ). As EVs can be internalized by an endocytic-like process, they may deliver regulatory biomolecules into vascular endothelial cells.…”
Section: Regulation Of Protumoral Functions Of Endothelial Cells By Tumor-derived Evsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor-derived EVs are thought to regulate protumoral functions of endothelial cells in numerous types of cancers including hepatocellular carcinoma (HCC) ( Lin et al, 2018 ), colorectal cancer ( Huang and Feng, 2017 ; Zeng et al, 2018 ; He et al, 2021 ), cervical cancer ( Wu et al, 2019 ), nasopharyngeal carcinoma ( Bao et al, 2018 ; Tian et al, 2021 ; Zhang K. et al, 2021 ), glioma ( Ma et al, 2017 ; Wang Z.-F. et al, 2019 ), and lung cancer ( Hsu et al, 2017 ). As EVs can be internalized by an endocytic-like process, they may deliver regulatory biomolecules into vascular endothelial cells.…”
Section: Regulation Of Protumoral Functions Of Endothelial Cells By Tumor-derived Evsmentioning
confidence: 99%
“…After taking up by human umbilical vein endothelial cells (HUVECs), miR-210 stimulates angiogenesis via down-regulating the expression of SMAD4 and STAT6 ( Lin et al, 2018 ). Vesicular miR-21-5p from colorectal cancer decreases Krev interaction trapped protein 1 expression to activate β-catenin signaling pathway and promote the expression of angiogenesis-related factors like VEGFA, thereby stimulating vascular permeability and angiogenesis ( He et al, 2021 ). In addition, cervical cancer-derived vesicular miR-221-3P promotes angiogenesis by inhibiting the expression of thrombospondin-2 in HUVECs, which consequently enhances tumor growth in vivo ( Wu et al, 2019 ).…”
Section: Regulation Of Protumoral Functions Of Endothelial Cells By Tumor-derived Evsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that both K562 and MEG01 are TP53-deficient CML cell lines, inhibition of CCND1 expression by miR-342-5p did lead to ATR-chk1 inhibition with ATM-chk2 activation and subsequent cell apoptosis (Fig. 5D-F ) [ 69 , 70 ]. We suggest that miR-342-5p expression directly or indirectly inhibits CCND1 and BCR-ABL expression, thereby possibly increasing ATM activation by dispersing BCR-ABL-associated ATM repression and reducing CCND1-ATR-Chk1-induced protection, as a result of ATM/ATR switching.…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNA-enriched exosomes promote angiogenesis via HIF-1 downregulation and overexpression of proangiogenic factors [47]. Recently, He et al suggested that ex-miR-21-5p is involved in angiogenesis and vascular permeability in CRC, by targeting trapped protein 1 (KRIT1) [48]. Notably, Simon et al have reported a potential EV-mediated mechanism for bevacizumab resistance in glioblastoma.…”
Section: Biological Mechanisms Of Exosomal Ncrnas In Crc Drug Resistancementioning
confidence: 99%